2002
DOI: 10.1094/mpmi.2002.15.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Induced Virus Resistance in Arabidopsis thaliana Is Independent of Pathogenesis-Related Protein Expression and the NPR1 Gene

Abstract: Salicylic acid (SA) treatment triggers inhibition of replication or movement of several positive-sense RNA plant viruses in tobacco. This resistance can also be stimulated by nonlethal concentrations of cyanide and antimycin A (AA) without triggering induction of pathogenesis-related PR-1 protein genes. In two ecotypes of Arabidopsis thaliana (Columbia and Nössen), SA-induced resistance to a tobamovirus, Turnip vein clearing virus (TVCV), was also induced by nonlethal concentrations of cyanide and AA without c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 54 publications
6
67
1
Order By: Relevance
“…Several reports indicate that treating plants with SA can inhibit the cell-to-cell movement of compatible viruses (Naylor et al, 1998;Murphy and Carr, 2002;Wong et al, 2002). We did not find this with CaMV.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Several reports indicate that treating plants with SA can inhibit the cell-to-cell movement of compatible viruses (Naylor et al, 1998;Murphy and Carr, 2002;Wong et al, 2002). We did not find this with CaMV.…”
Section: Discussioncontrasting
confidence: 78%
“…Wong et al (2002) reported that, in Arabidopsis, resistance to Turnip vein clearing tobamovirus (TVCV) was inducible by SA, cyanide, and antimycin A. Resistance to tobamoviruses appears to involve NPR1-independent inhibition of virus replication at the site of inoculation (Murphy and Carr, 2002;Wong et al, 2002). In contrast, SA-induced resistance to CMV appears to inhibit virus movement (Murphy et al, 2001), suggesting that, depending on the virus, defense may operate at different levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations have been reported for the effect of HCN on resistance to biotic and abiotic stresses after ethylene production. For example, cyanide enhances the resistance of tobacco (Nicotiana tabacum) and Arabidopsis leaves to tobacco mosaic virus and turnip vein clearing virus, respectively (Chivasa and Carr, 1998;Wong et al, 2002). It has also been suggested that cyanide, and not ethylene, is responsible for the resistance to blast fungus infection in young rice plants (Iwai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the induction of AOX by SA was not impaired in npr1 mutant plants. Based on these findings, it was proposed that NPR1 was not involved in the SA-induced resistance against TVCV (Wong et al, 2002). The role of NPR1 during compatible virus interactions was also investigated in A. thaliana plants infected with Oilseed rape mosaic virus (ORMV) (Huang et al, 2005).…”
Section: Rna Interference-mediated Resistancementioning
confidence: 99%